KNOWLEDGE OF THE POPULATION ABOUT SEXUALLY TRANSMITTED INFECTIONS IN THE DISTRICT OF PECÉM-CE, 2024 - Bezerra Feitosa de Amorim, Yana Carla; Mendes D’Angelo, Sarah; Maria de Almeida Lopes, Diana; by Souza Rosa, Ana Paula; Ithalo Francisco da Silva, Pedro; Cosme Rodrigues, Vanuza; Leandro Dias, Jeane; Iolanda da Silva, Maria; Ferreira de Andrade Neto, Valderi; de Maria Lopes de Carvalho, Conceição; Monik Morais de Oliveira, Bruna; de Sousa Tavares, Aurileide (Cadernos ESP, 2026)
Objective: To assess the knowledge, attitudes, and practices of the adult population regarding sexually transmitted infections (STIs). Methods: Descriptive, cross-sectional study using a household survey. Results: The sample was characterized, mostly, by female individuals (77.1%), aged between 20 and 69 years (86.6%), married (37.8%), with elementary school education (44.1%), heterosexual (95.5%), who earned between 0.5 and 1 minimum wage (37.8%). Regarding knowledge and attitudes, 92.9% reported having heard about STIs and 87.3% knew where to seek diagnosis and treatment. Meanwhile 89.9% were familiar with prevention methods. Regarding sexual behavior and health, 97.0% had already become sexually active and 71.6% had a steady partner, but only 30.3% used condoms. Conclusion: knowledge about STIs transmission and prevention was considered sufficient. However, the results do not guarantee safe sexual practices, as a considerable number of respondents did not use condoms during sexual intercourse.
Keywords: Disease Prevention; Sexually Transmitted Diseases; Sexual Behavior; Sexual Health; Health Knowledge, Attitudes, Practice